Influence of Effective Nucleon Mass on Equation of State for Supernova Simulations and Neutron Stars - Shuying Li; Junbo Pang; Hong Shen; Jinniu Hu; Kohsuke Sumiyoshi (The Astrophysical Journal)
We investigate the influence of the effective nucleon mass on the equation of state (EOS), which is constructed for simulations of core-collapse supernovae and binary neutron star mergers, within the relativistic mean-field (RMF) framework. The study introduces a new RMF parameter set, TM1m, which is a modification of the TM1e model with an adjusted effective mass, maintaining the saturation properties of nuclear matter. The TM1m model, with a larger effective mass ratio ( M ^* / M  ~ 0.8) compared to the TM1e model ( M ^* / M  ~ 0.63), is employed to construct a new EOS table, EOS5. This EOS table is designed to offer insights into the influence of the effective nucleon mass on the EOS within a relativistic framework, particularly above the saturation density. The results of EOS5 are compared with those obtained from other models, including both relativistic and nonrelativistic approaches. The properties of cold neutron stars, calculated using the TM1m model, are compatible with the existence of a 2 M _⊙ pulsar and the latest constraints on the tidal deformability and radii of a canonical 1.4 M _⊙ neutron star, derived from astrophysical observations.